The development of digital Malay ethnoparenting: “Preserving culture for parenting in digital age” - Ria Novianti; Mahdum; Suarman; Ainama Nafisa Putri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research aims to design and develop a Digital Malay Ethnoparenting application based on Riau Malay culture. Using the research and development method with a quantitative and qualitative approach, the research stages follow the ADDIE model. (Analysis, Design, Development, Implementation, Evaluation). The results of the analysis indicate the need for culturally-based parenting content that is relevant to the digital lifestyle of millennial parents. The application content is designed to include the values of Tunjuk Ajar Melayu, which contains moral and spiritual guidance. The application prototype was tested in alpha and beta phases, involving 48 parents in Pekanbaru. The trial showed that this application is innovative, easy to use, and meets the needs of modern parenting. Expert evaluation ensures the system's cultural validity and functionality. The research results confirm the potential of the application to preserve the cultural values of Riau Malay through technology, bridging the need for modernization without leaving behind the local cultural heritage.